2022
DOI: 10.1002/ange.202117587
|View full text |Cite
|
Sign up to set email alerts
|

Iodine‐Catalysed Dissolution of Elemental Gold in Ethanol

Abstract: Gold is a scarce element in the Earth's crust but indispensable in modern electronic devices. New, sustainable methods of gold recycling are essential to meet the growing eco-social demand of gold. Here, we describe a simple, inexpensive, and environmentally benign dissolution of gold under mild conditions. Gold dissolves quantitatively in ethanol using 2-mercaptobenzimidazole as a ligand in the presence of a catalytic amount of iodine. Mechanistically, the dissolution of gold begins when I 2 oxidizes Au 0 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…There have been numerous recent attempts to address these problems, e.g., by selective precipitation, 9, 10 chelation of aurate species using macrocyclic hosts, [11][12][13] 3D-printed scavenger filters, 14 direct one-pot conversion of elemental gold to organo-soluble complexes. [15][16][17][18] We have previously shown that mechanochemistry, which encompasses the use of mechanical forces like grinding and shearing to initiate, sustain, and conduct chemical transformations, 19 is a simple, rapid, and environmentally-friendly method to convert noble metals such as Pd, Au, and Pt into water-soluble salts. 20 Specifically, ball milling of these raw precious metals, either alone or in a mixture, with mild oxidants such as potassium peroxymonosulfate (2KHSO5•KHSO4•K2SO4, Oxone ® ), potassium persulfate (K2S2O8), or calcium hypochlorite (Ca(ClO)2) in the presence of simple halide salts results in tetrahaloaurate(III) [AuX4]¯, tetrahalopalladate(II) [PdX4] 2 ¯ or hexahaloplatinate(IV) [PtX6] 4 ¯ derivatives (X = Cl, Br) with a preference for gold oxidization.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous recent attempts to address these problems, e.g., by selective precipitation, 9, 10 chelation of aurate species using macrocyclic hosts, [11][12][13] 3D-printed scavenger filters, 14 direct one-pot conversion of elemental gold to organo-soluble complexes. [15][16][17][18] We have previously shown that mechanochemistry, which encompasses the use of mechanical forces like grinding and shearing to initiate, sustain, and conduct chemical transformations, 19 is a simple, rapid, and environmentally-friendly method to convert noble metals such as Pd, Au, and Pt into water-soluble salts. 20 Specifically, ball milling of these raw precious metals, either alone or in a mixture, with mild oxidants such as potassium peroxymonosulfate (2KHSO5•KHSO4•K2SO4, Oxone ® ), potassium persulfate (K2S2O8), or calcium hypochlorite (Ca(ClO)2) in the presence of simple halide salts results in tetrahaloaurate(III) [AuX4]¯, tetrahalopalladate(II) [PdX4] 2 ¯ or hexahaloplatinate(IV) [PtX6] 4 ¯ derivatives (X = Cl, Br) with a preference for gold oxidization.…”
Section: Introductionmentioning
confidence: 99%